Using Flaxseed, Yeast Extract and Psyllium as New Structuring Agents in Gluten-Free Bread: Quality Characteristics - Kaya, Handan Aydın; Cıngoz, Alı; Kaya, Cemal (My University, 2026)
Research into alternative hydrocolloids that can provide the necessary network structure for gluten-free bread production is ongoing. The aim of this study was to use alternative natural additives as gum substitutes in the production of gluten-free bread and to determine their effect on the quality characteristics of gluten-free bread. Yeast extract, flaxseed flour, and psyllium husk were used as gum substitutes in different proportions in the formulation. The formulations were determined using the complex lattice mixture design method. The physical, chemical, functional, textural, and sensory properties of gluten-free breads were determined. The use of ingredients alone has a negative effect on the physical and sensory properties of bread. Their use in mixtures improves the chemical, functional, and sensory properties of bread. Yeast extract increases the total antioxidant capacity and the phenolic content. However, it reduces the overall liking score. Psyllium husk powder increases the moisture content of bread and reduces baking losses. Consumers are seeking natural alternatives to products manufactured using chemical agents for both health and sensory reasons. Yeast extract, flaxseed flour, and psyllium are important alternatives to meet this demand.
Keywords: Bread; Gluten-free; Mixture design